Development of Web Based Web Based Digital Library as Learning Media in Cosmetology Education Program - Tanjung, Nurhayati; Nurul Rangkuti, Irmiah; Sitompul, Astrid; Ardhita Manda Putri, Wisri; Hanim Lubis, Habibah; Wahidah, Siti; Rezky Fauzani, Asrah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The problem raised in this study is the limited access of students to relevant, flexible, and appropriate learning resources according to the characteristics of the visual and practice-based Cosmetology field, which is one of the causes of students' lack of understanding of learning. This study aims to: (1) develop a web-based digital library as a learning medium in the Cosmetology Education Study Program. This study is a type of development research using ADDIE which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, interviews, and questionnaires. Product validity was assessed by two material experts and two media experts. Product trials were conducted in three stages, namely small group trials with 6 students, medium group trials with 12 students, and large group trials with 32 students. The results of the study showed that the product obtained an average feasibility score of 86.8% from material experts (very good category) and 94.8% from media experts (very good category). The small group trial obtained an average score of 80.9% (good), the medium group 86.8% (very good), and the large group 95.6% (very good). Based on expert evaluation and user trials, it can be concluded that this web-based digital library is appropriate and effective as a learning medium in the Makeup Education Program. The implications of this study indicate that a web-based digital library can be an alternative learning solution that not only improves students' learning independence, but also encourages the integration of technology in vocational learning.